Efficiency Estimation of Gum Arabic Production Cost in North and West Kordofan States, Sudan - Hassan, Mohammed Osman; Salih, Ali Abdelaziz; Ibrahim, Ibrahim Elnour; Eltahir, Muneer Elyas Siddig; Adam, Hassan Elnour; Tutu, Salih Omer; Alhabeeb, Hanan Elsadig (Journal of Marketing Studies, 2023)
Purpose: The aim of the study was to estimate the cost efficiency of gum Arabic Production under the applied free -trade policy in North and West Kordofan States. Methodology: Primary data was collected in 2016 by using a structured questionnaire and direct interviews with a sample of 100 gum Arabic producers; about 15% of the population of the study. Secondary data was collected from related official documents. Primary data was analyzed using, maximum-likelihood parameters of stochastic frontier cost function analytical methodology was used to estimate economic efficiency the level of the gum production cost. The factors of gum Arabic production tested were tapping tools, tapping labor, picking tools, picking labor, packing tools and transport. Findings: The coefficients of all these factors was found significant at 1% level of significance indicating the profitability of gum Arabic production. The mean economic efficiency for gum Arabic cost function was (0.97), indicating there is a likelihood increase of gum Arabic production by (97%). The cost efficiency range was between (81% to100 percent) only 2% lied between 61% to 80% range. This range implies that the cost efficiency of gum production was found to be high. As such, the variable cost of gum production was low since gum Arabic production needs only two main operations, tapping and picking. The tapping and picking tools were extremely of negligible cost. Unique Contribution to Theory, Policy and Practice: The study recommended getting benefit from low cost of gum Arabic production to allocate all the covered areas with gum trees, registering gum Arabic orchards, to provide a grantee for financing institutions.